Discrepancies between ALK protein disruption and occurrence of ALK gene rearrangement in Polish NSCLC patients - Grenda, Anna (J Thorac Dis, 2018)
BACKGROUND: Non-small cell lung cancer (NSCLC) patients with epidermal growth factor receptor (EGFR) mutations or anaplastic lymphoma kinase (ALK) rearrangement are predisposed to molecularly targeted therapies. Proper diagnostic is crucial for quick and correct patients qualification to optimal treatment method. Genetic tests to detect predictive factors could be performed sequentially. After excluding EGFR mutations, abnormal ALK protein expression should be tested using immunohistochemistry (IHC) method. In patients with disrupted ALK expression, the rearrangement of the ALK gene should be confirmed by FISH method. Despite few years of experience in analysis of these predictive factors, there are still problems in interpretation of diagnostic tests results. Especially, some recommendations for ALK IHC diagnosis are not precise. METHODS: Mutations in EGFR gene were examined using real-time PCR technique in 1,108 formalin-fixed paraffin-embedded (FFPE) tissues, 398 FFPE cell-blocks and 470 cytological specimens of NSCLC. The disrupted ALK protein expression was analysed in 1,100 samples including 782 histological and 306 cytological (cell-blocks) samples using IHC. Twelve materials (1.1%) were non-diagnostic in IHC. ALK gene rearrangement using FISH method was analysed in IHC positive cases. RESULTS: The frequency of EGFR mutations was 8.6%. EGFR mutations occurred significantly more often in females (P=0.00001, χ(2)=62.732) and in adenocarcinoma cases (P=0.0002, χ(2)=14.222). The exon 19 deletions (49%) and exon 21 Leu858Arg substitution (38%) were the most common, rare EGFR mutations occurred in 13% of patients. Any expression of abnormal ALK protein was detected in 202 cases (18.57%). ALK gene rearrangement was confirmed in 49 cases (4.5%). ALK gene rearrangement is significantly more common in female than in male (P=0.0105, χ(2)=6.541). In patients with ALK gene rearrangement, the median percentage of nuclei with ALK rearrangement was only 25.5%. The polysomy (≥4 gene copy number per nuclei) of ALK gene was observed in 39 cases (21.4% of patients with diagnostic result of FISH examination). Median number of ALK gene copy per nuclei was 2.9±0.77. Significant positive correlation between percentage of cells with abnormal ALK expression in IHC test and percentage of nuclei with ALK rearrangement in FISH method was detected (R=0.617, P<0.00001). Significant negative correlation between the number of copies of ALK gene and the percentage of cells with expression of abnormal ALK was observed (R=−0.2004, P<0.05). ALK gene rearrangement was significantly more frequently observed in the material with coarse-grained cytoplasmic and membranous IHC staining than in materials with light cytoplasmic stippling. The occurrence of cytoplasmic stippling correlated with the increase of ALK gene copy number. CONCLUSIONS: We indicated that diagnosis of ALK disruption in NSCLC patients should be notably careful using IHC and FISH methods. Recommendations for ALK diagnosis should include the way of interpretation of cases with low percentage of cells with abnormal ALK protein expression in IHC test, character of IHC reaction, and cases with ALK gene polysomy in FISH method.